Penatalaksanaan Holistik Pasien Asma Persisten Ringan Pada Perempuan Usia 12 Tahun dengan Faktor Pencetus Debu dan Cuaca Dingin Melalui Pendekatan Kedokteran Keluarga - Muhammad Reqza Pratama; Azelia Nusadewiarti (MAJORITY, 2022)
Asthma is a chronic inflammatory disorder of the airways that causes bronchial hyperreactivity that causes symptoms such as wheezing, coughing, shortness of breath and chest tightness, especially at night and early morning, which are generally reversible with or without treatment. The application of family doctor services based on evidence based medicine to patients by identifying risk factors, clinical problems, and management based on a problem solving framework with a patient-centered and family approach. This study is a Case Report. Primary data were obtained through history taking, physical examination, home visits to complete family and psychosocial data, as well as the environment. Assessment based on a holistic diagnosis from the beginning, process and end of the study quantitatively and qualitatively. In this patient, pharmacological and non-pharmacological interventions were carried out in the form of education in preventing asthma attacks in patients. Patient An. S, aged 12 years, had the main complaint of shortness of breath accompanied by coughing up phlegm at night. The patient was diagnosed with bronchial asthma and was already on medication. The patient's internal risk factor is having knowledge about the disease and the patient's home environment that is exposed to road dust. The external risk factor that affects is the state of the house that has but the windows are rarely opened. For the patients, it was done in the form of counseling about asthma, counseling on cleaning the home environment from dust, using masks when doing activities, and taking medication regularly. After the intervention, there was a change in the knowledge of the patient and his family.